The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1590/2179-8087.116317
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of dry tropical forest after three decades of vegetation suppression

Abstract: The aim of this study was to analyze the dynamics of the community and shrub-woody individuals in a dry forest in the Brazilian semiarid region after 29 years of vegetation suppression. Individuals with a circumference at 1.30 m above the ground (CBH) ≥ 6 cm were counted and their heights and CBH were measured in 40 permanent plots on three monitoring occasions (2011, 2013 and 2015). In the period between 2011 and 2015 the area presented a below average precipitation for the last 30 years. Phytosociological pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 27 publications
1
8
0
6
Order By: Relevance
“…No primeiro inventário em 2016 foram amostrados 835 indivíduos e no segundo em 2019 foram 787 indivíduos. Foi ainda registrado um decréscimo de 86 pela mortalidade e ganho de [44], observaram aumento na área basal.…”
Section: Mudanças Estruturaisunclassified
“…No primeiro inventário em 2016 foram amostrados 835 indivíduos e no segundo em 2019 foram 787 indivíduos. Foi ainda registrado um decréscimo de 86 pela mortalidade e ganho de [44], observaram aumento na área basal.…”
Section: Mudanças Estruturaisunclassified
“…The natural vegetation in this region is described as Shrub Savanna-steppe (Caatinga) (Melo et al, 2019) with a height between 3 and 15 m, and which during the wet period exhibit native tree-like shrub and herbaceous stratum species, while in the dry period show Leafless tree-like shrub species and bare soil. The experimental site is located in an area which underwent several years of selective wood extraction and which has a highly heterogeneous landscape characterized by tree-shrub vegetation, with deciduous species.…”
Section: Study Areamentioning
confidence: 99%
“…The sizes of the experimental plots used in phytosociological surveys mostly have dimensions varying between 100 m 2 and 400 m 2 ; smaller plots induce the need for more repetitions (Ferraz et al, 2013;Martins et al, 2017;Melo et al, 2019;Rodal et al, 2008aRodal et al, , 2008b. Ferraz et al (2013) found that the minimum number of sampling plots (plots with 400 m 2 ), which result in errors lower than 20%, is 22 units.…”
Section: Floristic Composition and Phytosociological Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…National territory and occupying the states of Bahia, Ceará, Piauí, Pernambuco, Rio Grande do Norte, Paraíba, Sergipe, Alagoas, Maranhão, besides the state of Minas Gerais that is outside the northeast region (Beuchle et al, 2015). Seasonal and periodic droughts establish intermittent river regimes and leave the vegetation without leaves (Melo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%